A force for change? The prospects for applying restorative justice to citizen complaints against the police in England and Wales - McLaughlin, Eugene (The British journal of criminology, 2002)
The rise of the victim support movement and the emergence of restorative justice practices have established the victim' as central to debate on criminal justice policy in the United Kingdom. However, victims of police misconduct have to date remained largely invisible within this debate. The aggrieved citizen is not allocated the morally validated status of victim' but the highly problematic status of complainant'. As a result, the police complaints system concentrates its efforts on interrogating her or his motives and complaints tend to be rendered unconvincing by the system. In many respects, the system acts to discipline or punish those citizens who have the temerity to lodge a complaint against police officers. It is now proposed, in the context of broader reforms, that the application of restorative justice principles will overcome the core problems associated with the police complaints system